2020
DOI: 10.14719/pst.2020.7.4.861
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-agronomic characters of oat growing with humic acid and zinc application in different sowing times

Abstract: The objectives of the study were to determine the effects of humic acid (HA) and zinc (Zn) applications on winter tolerance and yield performance of oat (cv. Albatros) planted in winter and spring sowing times (ST). We conducted the study in the 2017/2018 growing season. The experimental layout was split-split plots with three replications. Sowing times (winter and spring) comprised of the main plots. Humic acid application (with HA and without HA) was in the sub-plots, and Zn application rates (0, 23 and 46 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is essential to understand the plant-humic acid relationship properly in order to increase plant nutrient uptake [Peoples andCraswell 1992, Zhu et al 2001]. Recent studies have demonstrated that the concurrent application of humic acid and zinc can exert a positive influence on plants, leading to potential enhancements in yield and yield-related parameters [Hatami 2017, Kutlu andGulmezoglu 2020]. Insufficient zinc during development leads to a 50-70% drop in photosynthesis, varying with plant type and soil Zn levels.…”
mentioning
confidence: 99%
“…It is essential to understand the plant-humic acid relationship properly in order to increase plant nutrient uptake [Peoples andCraswell 1992, Zhu et al 2001]. Recent studies have demonstrated that the concurrent application of humic acid and zinc can exert a positive influence on plants, leading to potential enhancements in yield and yield-related parameters [Hatami 2017, Kutlu andGulmezoglu 2020]. Insufficient zinc during development leads to a 50-70% drop in photosynthesis, varying with plant type and soil Zn levels.…”
mentioning
confidence: 99%